Design of Arc Power Supply and Its Control System - ZHOU Cheng; TAO Hongliang; CAO Yang; ZHANG Min; CHEN Jielian; SUN Mao (Kongzhi Yu Xinxi Jishu)
According to requirements of low ripple target and fast current transfer for arc power supply, the main circuit was expounded and the control system base on DSP and CPLD was adopted to improve the performance of arc power supply. It described the main circuit and operation principle of arc power supply, and introduced the design of hardware and software of microcomputer control system based on DSP and CPLD. Experimental results indicate that the system has high precision of steady current, low ripple, rapid transfer of load current and adjustable current transfer depth etc..